Impact of Intellectual Capital on Organizational Performance of ICT SMEs in Penang, Malaysia - Jamal Abdul Nassir Shaari; Abu Hasan Bin Md Isa; Muhammad Khalique (Karachi institute of Economics and Technology, 2024)
Intellectual capital is a strategic asset for the growth and sustainability of SMEs. It contributes significantly towards the national economy, generating employment and improving the well-being of the public. The main purpose of this research was to determine how six components of intellectual capital affect the organizational performance of ICT SMEs operating in Penang, Malaysia. The developed model was tested through SEM and it adequately explained the effect of intellectual capital on organizational performance. The results suggest that customer capital has a significant positive influence on organizational performance of ICT SMEs while human capital, structural capital, social capital, technological capital and spiritual capital remained insignifi cant. Future studies may adopt a comparative approach to understand how intellectual capital affects organizational performance in emerging economies.